Exploring Reusability of Disposable Face Masks: Effects of Disinfection Methods on Filtration Efficiency, Breathability, and Fluid Resistance. Issue 11 (28th July 2021) - Teo, Jye Yng; Kng, Jessica; Periaswamy, Balamurugan; Liu, Songlin; Lim, Poh‐Chong; Lee, Chen Ee; Tan, Ban Hock; Loh, Xian Jun; Ni, Xiping; Tiang, Daniel; Yi, Guangshun; Ong, Yee Yian; et al.
Abstract: To curb the spread of the COVID‐19 virus, the use of face masks such as disposable surgical masks and N95 respirators is being encouraged and even enforced in some countries. The widespread use of masks has resulted in global shortages and individuals are reusing them. This calls for proper disinfection of the masks while retaining their protective capability. In this study, the killing efficiency of ultraviolet‐C (UV‐C) irradiation, dry heat, and steam sterilization against bacteria ( Staphylococcus aureus ), fungi ( Candida albicans ), and nonpathogenic virus ( Salmonella virus P22 ) is investigated. UV‐C irradiation for 10 min in a commercial UV sterilizer effectively disinfects surgical masks. N95 respirators require dry heat at 100 °C for hours while steam treatment works within 5 min. To address the question on safe reuse of the disinfected masks, their bacteria filtration efficiency, particle filtration efficiency, breathability, and fluid resistance are assessed. These performance factors are unaffected after 5 cycles of steam (10 min per cycle) and 10 cycles of dry heat at 100 °C (40 min per cycle) for N95 respirators, and 10 cycles of UV‐C irradiation for surgical masks (10 min per side per cycle). These findings provide insights into formulating the standard procedures for reusing masks without compromising their protective ability. Abstract : The ongoing coronavirus pandemic has resulted in global shortages of disposable face masks, prompting them to be reused. To ensure safe reuse, masks undergo various disinfection methods including ultraviolet‐C irradiation, dry heat, and steam sterilization. Particularly, five cycles of steam treatment (10 min per cycle) do not impair the filtration capabilities, breathability, and fluid resistance property of N95 respirators.